Outsmarting androgen receptor: creative approaches for targeting aberrant androgen signaling in advanced prostate cancer. Issue 3 (May 2011) - Knudsen, Karen E; Kelly, William Kevin
Prostatic adenocarcinomas are reliant on androgen receptor (AR) activity for survival and progression. Therefore, first-line therapeutic intervention for disseminated disease entails the use of AR-directed therapeutics, achieved through androgen deprivation and direct AR antagonists. While initially effective, recurrent, ''castrate-resistant'' prostate cancers arise, for which there is no durable means of treatment. An abundance of clinical study and preclinical modeling has led to the revelation that restored AR activity is a major driver of therapeutic failure and castrate-resistant prostate cancer development. The mechanisms underpinning AR reactivation have been identified, providing the foundation for a new era of drug discovery and rapid translation into the clinic. As will be reviewed in this article, these creative new ways of suppressing AR show early promise.